Travel Blogs: Genre and Topics - Stanislav V. Olenev; Nikita A. Slavnikov (Виртуальная коммуникация и социальные сети)
Online travel blogs are a phenomenon of auteur journalism. This article describes the genre specifics of Russian-language travel blogs posted on Youtube video hosting and its development prospects. The new multimedia journalism is highly adaptable, mobile, feasible, and independent. Travel writers used to be limited to a narrow segment of TV channels and magazines; modern travel bloggers develop their own style and do not have to conform to that of the editorial board. The research featured such travel bloggers as Anton Ptushkin, Leonid Pashkovsky, and Anton Lyadov. Each blog proved to be unique it its topics, genres, and methods of presentation, which means that this sector of auteur journalism has a great potential.